Measuring preoperative anxiety in patients undergoing elective surgery in Czech Republic - Pavlína Homzová; Renáta Zeleníková (University of Ostrava, 2015)
Aim: The main aim of the study was to measure preoperative anxiety in patients in the Czech Republic before elective surgery, using the Visual Analogue Scale for Anxiety (VAS-A). Design: A cross-sectional descriptive study. Methods: The sample consisted of 344 patients undergoing elective surgery. The day before surgery patients completed a questionnaire consisting of demographic data, the Amsterdam Preoperative Anxiety and Information Scale (APAIS) and the VAS-A. Spearman correlation was used to test correlation between the VAS-A and the subscales of the APAIS. Analysis of Variance (ANOVA) and the Kruskal-Walis test were used for group comparison. A p-value < 0.05 was considered to be significant. Results: Female patients and patients without previous experience of surgery had a significantly higher VAS-A score. The anxiety score measured by the VAS-A positively correlated with APAIS-Anxiety (r = 0.71) and its subscales. The results also showed that the most common anxieties resulted from postoperative pain, anaesthesiological complications, postoperative nausea and vomiting, concerns about regaining consciousness after anaesthesia, surgical errors, and postponement of surgery. Conclusion: The findings of this study support the utility of the VAS-A as a measure of preoperative anxiety. The VAS-A quickly and simply assesses anxiety and may be useful for research as well as clinical purposes when researchers or clinicians have very limited time.